Nest Hatch Chronology of Northern Bobwhite and Implications for Management - Frank L Loncarich; R. Kyle Hedges (National Quail Symposium Proceedings, 2022)
Managers in Missouri, USA, and in other Midwestern states have long operated under the belief that the peak of nest hatching for northern bobwhite (Colinus virginianus; hereafter, bobwhite) is 15 June. Though it is widely understood that bobwhite nests hatch throughout the summer, many management decisions are made based on the accepted peak. Fully understanding the dynamics behind bobwhite nest timing is critical, as management activities in nesting cover during summer are common. To better understand nest chronology, we used radio-telemetry to monitor nest incubation initiation, hatch date, and renesting rate on 6 conservation areas in southwestern Missouri from 2014 to 2018. Nest hatch date varied by area and year, but only 8.5% of nests hatched on or before 15 June. The 7-day interval during which the most nests hatched was 15–21 June, but we also saw high numbers of nests hatch in early July and mid- to late August. The median hatch date across all 5 years of the study was 17 July. Our results suggest that the entire summer is critical for bobwhite nesting activities, with late summer being just as important as the early summer months. We encourage bobwhite managers and conservation program policymakers across the Midwest to rethink previously held constructs of bobwhite nest timing. We also recommend that summer disturbances to nesting cover be kept to a minimum when the goal is to maximize bobwhite reproductive output.
Keywords: Colinus virginianus; nest timing; incubation; Missouri